Electric circuits - Kang, James S. (Cengage Learning, 2018)
You learn the basics of electric circuits with common design practices and simulations as the book presents clear step-by-step examples, practical exercises, and problems. Each chapter includes several examples and problems related to circuit design with answers for odd-numbered questions so you can further prepare yourself with self-guided study and practice. ELECTRIC CIRCUITS covers everything from DC circuits and AC circuits to Laplace transformed circuits. MATLAB scripts for certain examples give you an alternate method to solve circuit problems, check answers, and reduce laborious derivations and calculations. This edition also provides PSpice and Simulink examples to demonstrate electric circuit simulations.